Obesity, sedentary lifestyle and poor diet as risk factors for type 2 diabetes in young people: a literature review - Silvério, Diullia Antônia; Castro, Kelen Cristina Estavanate de; Silva, Juliana Lilis da; Amâncio, Natália de Fátima Gonçalves (JRG Journal of Academic Studies, 2024)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia resulting from dysfunctions in insulin production or action. Although previously rare among young individuals, the incidence of T2DM in this age group has been increasing alarmingly, driven by changes in dietary habits and physical inactivity, particularly in developed and developing countries. This article aimed to review the relationship between obesity, sedentary behavior, and unhealthy eating habits as risk factors for the development of T2DM in young people. The integrative review included 26 studies published between 2020 and 2024 in databases such as Google Scholar, Biblioteca Nacional de Saúde (BVS), Scientific Electronic Library Online (SciELO), and the National Library of Medicine (PubMed). The findings revealed that sedentary behavior, exacerbated by excessive use of electronic devices and the lack of infrastructure for physical activities, is a major risk factor. Furthermore, the high consumption of ultra-processed foods rich in sugars and saturated fats worsens obesity, often associated with insulin resistance. Adolescents from low-income backgrounds were identified as particularly vulnerable due to barriers in accessing healthy foods and opportunities for physical exercise. Conversely, studies indicated that diets rich in fiber, vegetables, and whole grains, combined with regular physical activity, significantly reduce the risk of T2DM. In conclusion, the rise of T2DM among young individuals results from interactions between behavioral, socioeconomic, and environmental factors. Public policies that promote access to healthy food, encourage physical activity, and educate the population about the risks of sedentary lifestyles and poor dietary habits are crucial to curbing this growing trend.